Electrode protection member and all-solid-state battery including same

By using an electrode protection member that combines composite resin with hydroxy-functionalized carbon-based tubular body in an all-solid state battery, the problem of possible internal short circuits and resin infiltration in lithium all-solid state battery under high temperature and high pressure conditions is solved, and the battery stability is achieved performance and performance improvement.

CN119495914APending Publication Date: 2025-02-21HYUNDAI MOTOR CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410386593.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-18
Filing Date
2024-04-01
Publication Date
2025-02-21

Smart Images

  • Figure CN119495914A_ABST
    Figure CN119495914A_ABST
Patent Text Reader

Abstract

The present invention provides an electrode protection member, a method of manufacturing the same, and an all-solid-state battery including the same, the electrode protection member including a lower structure including a carbon-based tubular body whose surface is functionalized with a hydroxyl group, and a composite resin portion including a thermosetting resin and an ultraviolet curable resin disposed on the lower structure.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims the benefit of Korean Patent Application No. 10-2023-0108575 filed in the Korean Intellectual Property Office on August 18, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0002] The present invention relates to an electrode protection member for protecting an all-solid-state battery from an internal short circuit, and an all-solid-state battery including the electrode protection member. Background Art

[0003] Due to the depletion of fossil fuels and the increasing demand for sustainable energy, research on low-cost, environmentally friendly, high-performance energy conversion and storage devices, especially lithium secondary batteries, has progressed rapidly. The application scope of lithium secondary batteries is constantly expanding, and they can be used not only in small electronic devices, but also as medium and large power devices for electric vehicles and energy storage systems (ESS).

[0004] In particular, as lithium secondary batteries are used as energy sources for electric vehicles, the demand for high-output and high-energy-density lithium secondary batteries is rapidly increasing. However, existing lithium secondary batteries using flammable liquid electrolytes have limitations, such as leakage, fire, and explosion safety issues due to rapid changes in internal and external environments such as temperature changes and external shocks. Therefore, it is necessary to use solid electrolytes with more stable and longer life characteristics to replace existing flammable liquid electrolytes.

[0005] However, in a lithium all-solid-state battery using a solid electrolyte, the area of ​​the negative electrode coated with the solid electrolyte is larger than that of the positive electrode, so an internal short circuit is very likely to occur under high temperature and high pressure conditions. To solve this problem, a method based on a mixed SiO 2 、MgO、ZnO、Na 2 O、Al 2 O 3 However, since the step formed by the difference in area between the negative electrode and the positive electrode was not fully protected, cracks occurred under pressure.

[0006] In addition, a method of using a curing resin such as a thermosetting resin or an ultraviolet curing resin in addition to a solid material has been proposed. However, when a thermosetting resin or an ultraviolet curing resin is applied to a solid electrolyte layer, there is a limitation that each resin penetrates into the solid electrolyte layer, causing a side reaction, or penetrates into the contact surface with the positive electrode.

[0007] Therefore, it is necessary to develop an electrode protection component that can prevent internal short circuits in all-solid-state batteries and inhibit side reactions. Summary of the invention

[0008] The object of the present invention is to solve the above-mentioned problems and provide an electrode protection component, which prevents each resin from penetrating into the positive electrode, inhibits side reactions in an all-solid-state battery, and firmly bonds with the electrode and the solid electrolyte layer by arranging a composite resin including a thermosetting resin and a UV-curable resin on a carbon-based tubular body whose surface is functionalized with hydroxyls.

[0009] In one aspect, an electrode protection member is provided, comprising 1) a lower structure including a carbon-based body whose surface contains one or more hydroxyl groups or is functionalized with one or more hydroxyl groups; and 2) a composite resin part disposed on the lower structure, the composite resin part including a thermosetting resin and an ultraviolet curable resin.

[0010] In certain aspects, the carbon-based body is a tubular body. The carbon-based body can also have other structures.

[0011] An exemplary embodiment of the present invention provides an electrode protection member including a lower structure including a carbon-based tubular body whose surface is functionalized with a hydroxyl group; and a composite resin portion including a thermosetting resin and an ultraviolet curing resin provided on the lower structure.

[0012] The substructure may be a porous plate-shaped structure in which a plurality of carbon-based tubular bodies are connected to each other by point contact. The porosity of the porous plate-shaped structure is about 60% to about 95%. The substructure may be a web-shaped plate-shaped structure in which a plurality of carbon-based tubular bodies are irregularly connected. The substructure may be a grid-shaped plate-shaped structure in which a plurality of carbon-based tubular bodies are regularly connected.

[0013] The carbon-based tubular body may be solid or hollow. The carbon-based tubular body may include at least one or more selected from the group consisting of carbon fibers, carbon nanotubes, graphene, and mixtures thereof. The surface of the carbon-based tubular body may be functionalized with one or more hydroxyl groups or treated to provide one or more hydroxyl groups, for example, by treating with a peroxide-based compound or other suitable agent.

[0014] The carbon-based body mentioned herein (including carbon-based tubular body), the carbon-based body can include at least or up to about 10 weight %, 20 weight %, 30 weight %, 40 weight %, 50 weight %, 60 weight %, 70 weight %, 80 weight %, 90 weight %, 95 weight %, 98 weight %, 99 weight % or 100 weight % carbon based on the total weight of the carbon-based body. In some aspects, based on the total weight of the carbon-based body, the carbon-based body can include at least or up to about 50 weight %, 60 weight %, 70 weight %, 80 weight %, 90 weight %, 95 weight %, 98 weight %, 99 weight % or 100 weight % carbon. In other aspects, the carbon-based body can include at least or up to about 80 weight %, 90 weight %, 95 weight %, 98 weight %, 99 weight % or 100 weight % carbon based on the total weight of the carbon-based body.

[0015] The thermosetting resin may be a polyurethane-based polymer. The polyurethane-based polymer may contain an OH functional group and an NCO functional group in a molar ratio of about 1:1.4 to about 1:1.8.

[0016] The ultraviolet curable resin may include an acrylate-based polymer, a reactive diluent, and a photopolymerization initiator. The ultraviolet curable resin and the thermosetting resin may be included in a weight ratio of about 1:0.4 to about 1:1.

[0017] In certain embodiments, the average thickness of the lower structure is from about 10 μm to about 40 μm.

[0018] The carbon-based tubular body in the lower structure and the thermosetting resin in the composite resin portion may be connected to each other via a urethane bond.

[0019] In addition, another embodiment of the present invention provides an all-solid-state battery, which includes a negative electrode; a solid electrolyte layer arranged on the surface of the negative electrode; a positive electrode arranged on the surface (e.g., the center) of the solid electrolyte layer; and an electrode protection member arranged on the surface of the solid electrolyte layer where the positive electrode is not arranged (e.g., the end side).

[0020] The electrode protection member is provided in an area of ​​about 5% to about 10% of the contact area between the negative electrode and the solid electrolyte layer.

[0021] Another embodiment of the present invention provides a method for manufacturing an all-solid-state battery, the method comprising the following steps: in a laminate, a lower structure is arranged and pressed on a surface (e.g., an end side) of a solid electrolyte layer where a positive electrode is not arranged, the lower structure comprising a carbon-based tubular body whose surface is functionalized with hydroxyls, wherein the laminate comprises a negative electrode, a solid electrolyte layer arranged on the surface of the negative electrode, and a positive electrode arranged on the surface (e.g., the center) of the solid electrolyte layer; a mixture comprising a thermosetting compound and an ultraviolet-curing compound is arranged on the lower structure, and the thermosetting compound is cured; and the ultraviolet-curing compound is cured by irradiating the mixture with ultraviolet rays to form a composite resin portion.

[0022] The calendering may be performed at a temperature of about 20° C. to about 30° C. and a pressure of about 2 MPa to about 6 MPa.

[0023] The dose of UV radiation can be about 1000 mW / cm 2 About 1500mW / cm 2 , the speed can be about 30 mm / s to about 40 mm / s.

[0024] The viscosity of the mixture for forming the composite resin part is about 10,000 Cp to about 15,000 Cp.

[0025] By using the electrode protection member of the present invention and the all-solid-state battery containing the same, various resins used as the electrode protection member can be prevented from penetrating into the electrode and the solid electrolyte layer, thereby suppressing the side reactions caused by the penetration. In addition, by preventing the step generated by the area difference between the electrodes, an all-solid-state battery with a high stacking structure can be realized.

[0026] Furthermore, the thermosetting resin contained in the composite resin portion forms a urethane bond with the lower structure (including the carbon-based tubular body functionalized with a hydroxyl group), and the resin is further finally cured by ultraviolet rays, thereby firmly bonding the composite resin portion to the lower structure.

[0027] As used herein, the term "all-solid-state battery" includes a rechargeable battery that includes a solid electrolyte for transferring ions between the battery electrodes. In certain aspects, the battery can be a secondary battery.

[0028] In another aspect, a vehicle comprising a battery disclosed herein is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a diagram schematically illustrating a manufacturing process of an all-solid-state battery including an electrode protection material according to an exemplary embodiment of the present invention.

[0030] Figure 2 is a diagram illustrating in detail the structure of an electrode protective material according to an exemplary embodiment of the present invention.

[0031] Figure 3A This graph shows the degree of curing based on the weight ratio of thermosetting resin and UV curing resin.

[0032] Figure 3B are SEM and CT images of the solid electrolyte layer in contact with the electrode protective material in the all-solid-state battery according to Example 1.

[0033] Figure 3C These are SEM and CT images of the solid electrolyte layer in contact with the electrode protective material in the all-solid-state battery according to Comparative Example 1.

[0034] Figure 4 3 is a graph illustrating the capacity retention rate of the all-solid-state batteries according to Example 1 and Comparative Example 1 during the cycle. DETAILED DESCRIPTION

[0035] The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" used herein are also intended to include plural forms. These terms are only used to distinguish one element from another element and do not limit the properties, sequence or order of the constituent elements. It should be further understood that the terms "comprises" and / or "comprising" used in this specification indicate the presence of the features, integers, steps, operations, elements and / or elements, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, elements and / or their groups. As used herein, the term "and / or" includes any and all combinations of one or more related listed items. Throughout the specification, unless there is a clear contrary description, the word "comprise" and variations such as including (comprises) or including (comprising) should be understood to include the elements without excluding any other elements. In addition, the terms "unit", "-er", "-device" and "module" described in the specification refer to units for processing at least one function and operation, which can be implemented by hardware elements or software elements and their combinations.

[0036] Although the exemplary embodiments are described as using multiple units to perform the exemplary process, it is understood that the exemplary process can also be performed by one or more modules. In addition, it is understood that the term controller / control unit refers to a hardware device including a memory and a processor that is specifically programmed to perform the process described herein. The memory is configured to store the modules, and the processor is specifically configured to execute the modules to perform one or more processes further described below.

[0037] Unless otherwise specified or apparent from the context, the term "about" as used herein is understood to be within the normal tolerance range in the art, such as within 2 standard deviations of the mean. "About" may be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the stated value. Unless the context indicates otherwise, all numerical values ​​provided herein are modified by the term "about".

[0038] An electrode protection member and an all-solid-state battery including the same will be described in detail below so that those skilled in the art can easily implement the present invention.

[0039] An electrode protection member according to an exemplary embodiment of the present invention includes a lower structure including a carbon-based tubular body whose surface is functionalized with a hydroxyl group, and a composite resin portion including a thermosetting resin and an ultraviolet curing resin provided on the lower structure.

[0040] The lower structure may be a porous plate-like structure in which a plurality of carbon-based tubular bodies are interconnected by point contact. Specifically, the lower structure may be a mesh plate-like structure in which a plurality of carbon-based tubular bodies are irregularly connected. Alternatively, the lower structure may be a mesh plate-like structure in which a plurality of carbon-based tubular bodies are regularly connected. However, as long as the lower structure can provide a space for accommodating the composite resin portion, the shape of the lower structure is not necessarily limited thereto.

[0041] The porosity of the porous plate-like structure may be about 60% to about 95%, preferably about 65% to about 90%, and more preferably about 70% to about 85%. The porosity here refers to the ratio of the total pore volume present in the porous plate-like structure to the total volume of the porous plate-like structure. Meanwhile, the porosity of the porous plate-like structure can be measured using methods such as mercury intrusion porosimetry (MIP).

[0042] When the porosity of the porous plate-like structure satisfies the above numerical range, sufficient space can be provided to accommodate the composite resin part, thereby promoting the combination of the lower structure and the composite resin part.

[0043] The average thickness of the lower structure may be about 10 μm to about 40 μm, preferably about 15 μm to about 35 μm, and more preferably about 20 μm to about 30 μm. When the average thickness of the plate-like structure satisfies the above numerical range, it is possible to effectively prevent side reactions caused by the composite resin portion penetrating the solid electrolyte layer disposed on the surface of the negative electrode, and protect the step formed by the area difference between the negative electrode and the positive electrode.

[0044] The carbon-based body may be solid or hollow.

[0045] The carbon-based body may include at least one or more selected from the group consisting of carbon fibers, carbon nanotubes, graphene, and mixtures thereof.

[0046] Specifically, the carbon nanotube may include at least one selected from the group consisting of a single-walled carbon nanotube, a double-walled carbon nanotube, a multi-walled carbon nanotube, and a bundled carbon nanotube.

[0047] The surface of the carbon-based host can be suitably functionalized with hydroxyl groups through the treatment with peroxide-based compounds.

[0048] For example, the peroxide-based compound may include, for example, i) hydrogen peroxide; ii) a compound selected from the group consisting of peroxydiphosphoric acid (H 4 P 2 O 8 ), disulfuric acid peroxide (H 4 S 2 O 8 ), phthalimidoperoxycaproicacid, peracetic acid (C 2 H 4 O 3 ), peroxybenzoic acid, diperoxyphthalic acid and their salts; or iii) at least one selected from the group consisting of benzoyl peroxide, methyl ethyl ketone peroxide, dicumyl peroxide and tert-butyl cumyl peroxide.

[0049] By functionalizing the surface of the carbon-based body with hydroxyl groups, the carbon-based body can form a more robust bond with the composite resin included in the electrode protection member accommodated in the lower structure including the carbon-based tubular body.

[0050] Specifically, the carbon-based body in the lower structure and the thermosetting resin in the composite resin part can be connected to each other through a urethane bond. That is, the hydroxyl groups coated on the surface of the carbon-based body form a urethane bond with the thermosetting resin in the composite resin, thereby firmly connecting the carbon-based body and the composite resin.

[0051] The thermosetting resin can be a polyurethane-based polymer. A polyurethane-based polymer refers to a polymer containing a urethane repeating unit formed by the reaction of an isocyanate and a polyol in the main chain. In this case, an isocyanate is a compound having 2 or more NCO groups, and a polyol is a compound having 3 or more hydroxyl groups.

[0052] The NCO groups of the polyurethane-based polymer contained in the thermosetting resin react with the hydroxyl groups on the surface of the carbon-based tubular body in the lower structure to form urethane bonds, thereby primarily bonded the lower structure and the composite resin portion.

[0053] The isocyanate may include at least one or more selected from the group consisting of toluene diisocyanate (TDI), 4,4-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), tolidine diisocyanate (TODI), cyclohexane diisocyanate (HMDI), isophorone diisocyanate (IPDI), p-phenylene diisocyanate, trans-cyclohexane, 1,4-diisocyanate, xylene diisocyanate (XDI) and mixtures thereof, but is not necessarily limited thereto.

[0054] Examples of the polyol may include, but are not limited to, polyether-based polyol, polyester-based polyol, polycarbonate-based polyol, or polyalkylene-based polyol.

[0055] The polyether-based polyol can be obtained by adding alkylene oxide to a polyol having 3 or more hydroxyl groups (such as trimethylolpropane, glycerol, or pentaerythritol). For example, the alkylene oxide may be ethylene oxide or propylene oxide.

[0056] Polyester-based polyols can be obtained by reacting low molecular weight diols, low molecular weight dicarboxylic acids and triols.

[0057] The low molecular weight diol may include, for example, ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butadienediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, cyclohexanediol, and the like.

[0058] The low molecular weight dicarboxylic acid may include, for example, terephthalic acid, isophthalic acid, 1,5-naphthoic acid, 2,6-naphthoic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylene dicarboxylic acid, dodecamethylene dicarboxylic acid, and the like.

[0059] Examples of the triol may include trimethylolpropane, glycerin, and the like.

[0060] Examples of the polycarbonate-based polyol may include polyhexamethylene carbonate polyol, polycyclohexanedimethylene carbonate polyol, and the like.

[0061] Examples of the polyalkylene polyol may include polybutadiene polyol, hydrogenated polybutadiene polyol, hydrogenated polyisoprene polyol, and the like.

[0062] The polyurethane-based polymer may contain OH functional groups and NCO functional groups in a molar ratio of about 1:1.4 to about 1:1.8, preferably about 1:4.5 to about 1:7.5, and more preferably about 1:1.5 to about 1:1.7. When the molar ratio of the hydroxyl functional group and the NCO functional group in the polyurethane polymer satisfies the above numerical range, a polyurethane-based compound having a three-dimensional structure may be formed, the terminal of the compound having an NCO functional group, which may be cross-linked with a hydroxyl group on the surface of the carbon-based tubular body contained in the lower structure, thereby forming a strong urethane bond.

[0063] The ultraviolet curable resin may include an acrylate-based polymer, a reactive diluent, and a photopolymerization initiator. The ultraviolet curable resin may combine the lower structure and the composite resin part together through a curing reaction under ultraviolet irradiation, thereby forming a more robust electrode protection member.

[0064] Acrylate-based polymers can form a cured film, can affect the physical properties of the final UV-curable resin, and can achieve photocuring through the acrylate groups, which are reactive sites for UV curing by ultraviolet light.

[0065] The acrylate-based polymer may include at least one or more selected from the group consisting of epoxy acrylate, polyurethane acrylate, polyester acrylate, polyether acrylate, and silicone acrylate.

[0066] Reactive diluents can be used as crosslinking agents for acrylate-based polymers and can be used to adjust the viscosity of UV-curable resins to an appropriate range.

[0067] The reactive diluent may include a radical photocurable compound. Specifically, the reactive diluent may include a monofunctional acrylate-based monomer.

[0068] The monofunctional acrylate-based monomer may include at least one or more selected from the group consisting of methyl methacrylate (MMA), ethyl methacrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethyl acrylate (HEA), glycidyl methacrylate (GMA), 2-hydroxyethyl methacrylate (2-hydroxyethyl methacrylate, 2-HEMA), acryloyl morpholine (ACMO), isobornyl acrylate (IBOA), 2-hydroxypropyl methacrylate (2-hydroxy propyl methacrylate, 2-HPMA), hydroxypropyl acrylate (HPA), ethoxyethoxy ethyl acrylate (EOEOEA), butyl acrylate (BA) and mixtures thereof, but is not necessarily limited thereto.

[0069] The photopolymerization initiator can be used to initiate polymerization by absorbing ultraviolet rays and generating free radicals or cations.

[0070] The photopolymerization initiator may include a benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, benzoin isobutyl ether, ether), acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-propan-1-one, 4-(2-hydroxyethoxy)phenyl-2(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methyl At least one or more of the group consisting of anthraquinone, 2-ethylanthraquinone, 2-tertiary-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyldimethylketal, acetophenone dimethylketal and p-dimethylaminobenzoate, but not necessarily limited thereto.

[0071] The weight ratio of the ultraviolet curable resin to the thermosetting resin may be about 1:0.4 to about 1:1, preferably about 1:0.4 to about 1:0.6. When the weight ratio of the thermosetting resin to the ultraviolet curable resin satisfies the above numerical range, the curing rate of the composite resin may be further increased and may be completely cured, thereby preventing the composite resin from impregnating (or penetrating) into the solid electrolyte layer of the all-solid-state battery.

[0072] Another embodiment of the present invention provides an all-solid-state battery, which includes a negative electrode; a solid electrolyte layer arranged on the surface of the negative electrode; a positive electrode arranged on the surface of the solid electrolyte layer (e.g., the center); and an electrode protection member arranged on the surface of the solid electrolyte layer where the positive electrode is not arranged (e.g., the end side).

[0073] The negative electrode may be manufactured by coating a slurry containing a negative electrode active material, a binder, and a conductive material on a negative electrode current collector.

[0074] The negative electrode active material may include, for example, one or more selected from the group consisting of natural graphite, artificial graphite, carbonaceous material; lithium-containing titanium composite oxide (LTO), Si, SiOx, Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe metal (Me); an alloy composed of the above metal (Me); an oxide (MeOx) of the above metal (Me); and a composite material of the above metal (Me) and carbon.

[0075] For example, the binder may include one or more selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, recycled cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber and copolymers thereof.

[0076] The conductive material may include graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjenblack, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, but are not necessarily limited thereto. Any material that has conductivity and does not cause chemical changes in the battery can be used as the conductive material.

[0077] The negative electrode current collector may include, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum cadmium alloy, etc.

[0078] The type of solid electrolyte contained in the solid electrolyte layer may include, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or a polymer-based solid electrolyte, etc., but is not particularly limited thereto.

[0079] The sulfide-based solid electrolyte may include a compound represented by the following formula (1).

[0080] [Formula 1]

[0081] M 1 a M 2 b S c X 1 d

[0082] In Formula 1, M 1 is one or more selected from alkali metals and alkaline earth metals, M 2 is Sb, Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or La, X 1 is F, Cl, Br, I, O, Se or Te, 0 < a ≤ 6, 0 < b ≤ 6, 0 < c ≤ 6 and 0 ≤ d ≤ 6.

[0083] The oxide-based solid electrolyte may include those selected from the group consisting of LLTO-based compounds, Li 6 La 2 CaTa 2 O 12 、Li 6 La 2 ANb 2 O 12 (A = Ca or Sr), Li 2 Nd 3 TeSbO 12 、Li 3 BO 2.5 N 0.5 、Li9 SiAlO 8 , LAGP-based compounds, LATP-based compounds, Li 1+ a1 Ti 2-a1 Al a1 Si b1 (PO 4 ) 3-b1 (where 0≤a1≤1, 0≤b1≤1), LiAl a2 Zr 2-a2 (PO 4 ) 3 (where 0≤a2≤1), LiTi a3 Zr 2-a3 (PO 4 ) 3 At least one or more of the group consisting of (wherein 0≤a3≤1), LISICON-based compounds, LIPON-based compounds, perovskite-based compounds, nasicon-based compounds and LLZO-based compounds.

[0084] The polymer-based solid electrolyte may include, for example, one or more selected from the group consisting of a polyether-based polymer, a polycarbonate-based polymer, an acrylate-based polymer, a polysiloxane-based polymer, a phosphazene-based polymer, a polyethylene derivative, an alkylene oxide derivative such as polyethylene oxide (PEO), a phosphate polymer, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and a polymer containing an ionically dissociable group, but is not necessarily limited thereto.

[0085] The positive electrode may be manufactured by coating a slurry containing a positive electrode active material, a binder, and a conductive material on a positive electrode current collector.

[0086] The positive electrode active material may include, for example, lithium manganese-based oxides such as LiMnO 2 、LiMn 2 O 4 , lithium cobalt-based oxides, such as LiCoO 2 , lithium nickel-based oxides, such as LiNiO 2 , lithium nickel manganese cobalt-based oxides, such as Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3) 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.5 Mn 0.3 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 and Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 , or lithium-nickel-cobalt-aluminum oxides, such as Li(Ni 0.8 Co 0.15 Al 0.05 ) 2 , but not necessarily limited to this.

[0087] The binder and the conductive material may be the same as those described for the negative electrode.

[0088] The positive electrode current collector may include, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, aluminum, or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.

[0089] The area where the electrode protection member is provided may account for about 5% to about 10% of the contact area between the negative electrode and the solid electrolyte layer, preferably about 5.5% to about 9.5%, and more preferably about 6% to about 9%.

[0090] A solid electrolyte layer having the same area as the negative electrode is arranged on the surface of the negative electrode, and the positive electrode is arranged on the solid electrolyte layer, in particular, at the center of the solid electrolyte layer. In particular, the area of ​​the negative electrode and the solid electrolyte layer is larger than the area of ​​the positive electrode. Therefore, due to this difference in area, the remaining area of ​​the solid electrolyte layer (excluding the positive electrode arranged on the surface (e.g., the center) of the solid electrolyte layer) may be exposed to the outside. The all-solid-state battery according to the present invention has a structure in which an electrode protection member is arranged on the surface (e.g., the end side) of the solid electrolyte layer where the positive electrode is not arranged. Through this structure, the area difference caused by the positive electrode area being smaller than the solid electrolyte layer area can be eliminated, and the electrode protection member can be used to cover the part of the area of ​​the solid electrolyte layer exposed to the outside.

[0091] By arranging the electrode protection member of the present invention on the surface of the solid electrolyte layer where the positive electrode is not arranged (e.g., the end side), cracks can be prevented from occurring under pressurized conditions during the manufacturing process of the all-solid-state battery. In addition, when using conventional thermosetting resins or ultraviolet curing resins, the resin will penetrate into the solid electrolyte layer, causing side reactions, or penetrate into the positive electrode, forming steps due to the area difference between the electrodes, resulting in unstable electrodes when forming a laminated structure. On the contrary, in the present invention, by using an electrode protection member, side reactions can be suppressed to form an all-solid-state battery with a high stack structure.

[0092] Another embodiment of the present invention also provides a method for manufacturing an all-solid-state battery, the method comprising the following steps: in a stack, a lower structure is arranged and rolled on a surface (e.g., an end side) of a solid electrolyte layer where a positive electrode is not arranged, the lower structure comprising a carbon-based tubular body whose surface is functionalized with hydroxyls, wherein the stack comprises a negative electrode, a solid electrolyte layer arranged on the surface of the negative electrode, and a positive electrode arranged on the surface (e.g., the center) of the solid electrolyte layer; a mixture comprising a thermosetting compound (i.e., a compound cured by heat) and an ultraviolet-curing compound (i.e., a compound cured by ultraviolet rays) for forming a composite resin part is arranged on the lower structure, and the thermosetting compound is cured; and the ultraviolet-curing compound is cured by irradiating the pressurized mixture (pressurized mixture) for forming the composite resin part with ultraviolet rays.

[0093] First, in a laminate, a step of arranging and rolling a lower structure including a carbon-based tubular body functionalized with a hydroxyl group is performed on a surface (e.g., an end side) of a solid electrolyte layer where no positive electrode is arranged. The laminate includes a negative electrode, a solid electrolyte layer arranged on the surface of the negative electrode, and a positive electrode arranged on the surface (e.g., the center) of the solid electrolyte layer.

[0094] Here, with respect to the negative electrode, the positive electrode, the solid electrolyte layer, and the lower structure, the descriptions of the electrode protection member and the all-solid-state battery also apply.

[0095] Pressurization can be performed at a temperature of about 20°C to about 30°C and a pressure of about 2MPa to about 6MPa, preferably about 2.5MPa to about 5.5MPa, and more preferably about 3MPa to about 5MPa. When pressurization is performed under the above pressure conditions, the porosity of the lower structure reaches about 60% to about 95%, preferably about 65% to about 90%, and more preferably about 70% to about 85%, thereby providing sufficient space to accommodate the composite resin part. The average thickness of the lower structure is about 10μm to about 40μm, preferably about 15μm to about 35μm, and more preferably about 20μm to about 30μm, so that the occurrence of side reactions caused by the composite resin part penetrating into the solid electrolyte layer disposed on the surface of the negative electrode can be effectively suppressed, and the steps formed due to the area difference between the negative electrode and the positive electrode are protected.

[0096] Meanwhile, the pressurization may be performed for about 4 seconds to about 11 seconds, preferably about 5 seconds to about 10 seconds.

[0097] Next, a step of providing a mixture for forming a composite resin part including a thermosetting compound and an ultraviolet curing compound on the lower structure and curing the thermosetting compound is performed.

[0098] The thermosetting compound may include a polyurethane-based polymer. The polyurethane-based polymer may contain an OH functional group and an NCO functional group in a molar ratio of about 1:1.4 to about 1:1.8, preferably about 1:4.5 to about 1:7.5, and more preferably about 1:1.5 to about 1:1.7. When the molar ratio of the OH functional group and the NCO functional group in the polyurethane-based polymer satisfies the above numerical range, a polyurethane-based compound having an NCO functional group at the end of a three-dimensional structure may be formed, which may be cross-linked with a hydroxyl group on the surface of a carbon-based tubular body contained in the lower structure, thereby forming a strong urethane bond.

[0099] When the mixture for forming the composite resin part is applied to the lower structure, the NCO group of the thermosetting compound in the mixture for forming the composite resin part and the hydroxyl group on the surface of the carbon-based tubular body contained in the lower structure in contact with the mixture for forming the composite resin part may first react to form a urethane bond. In this case, the mixture for forming the composite resin part may be in a semi-cured state that is not completely cured.

[0100] Finally, a step of curing the ultraviolet curing compound by irradiating ultraviolet rays to the pressurized mixture for forming the composite resin portion is performed.

[0101] The ultraviolet curable compound may include an acrylate-based polymer, a reactive diluent, and a photopolymerization initiator. The ultraviolet curable compound may further combine the lower structure and the components for forming the composite resin portion together through a curing reaction irradiated by ultraviolet light, thereby forming a more robust electrode protection member. In this case, the composition for forming the composite resin portion may be in a fully cured state.

[0102] Acrylate-based polymers form cured films, can affect the physical properties of the final UV-curable resin, and can enable photocuring via the acrylate groups, which are reactive sites for UV curing via ultraviolet light.

[0103] The acrylate-based polymer may include at least one or more selected from the group consisting of epoxy acrylate, polyurethane acrylate, polyester acrylate, polyether acrylate, and silicone acrylate.

[0104] The reactive diluent acts as a crosslinking agent for the acrylate-based polymer and can be used to adjust the viscosity of the UV-curable resin to an appropriate range.

[0105] The reactive diluent may include a free radical photocurable compound. Specifically, the reactive diluent may include a monofunctional acrylate-based monomer.

[0106] The monofunctional acrylate-based monomer may include at least one or more selected from the group consisting of methyl methacrylate (MMA), ethyl methacrylate, propyl (meth) acrylate, butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, dodecyl (meth) acrylate, stearyl (meth) acrylate, methoxyethyl (meth) acrylate, ethoxyethyl (meth) acrylate, ethyl acrylate (HEA), glycidyl methacrylate (GMA), 2-hydroxyethyl methacrylate (2-HEMA), acryloyl morpholine (ACMO), isobornyl acrylate (IBOA), 2-hydroxypropyl methacrylate (2-HPMA), hydroxypropyl acrylate (HPA), ethoxyethoxyethyl acrylate (EOEOEA), butyl acrylate (BA) and mixtures thereof, but is not necessarily limited thereto.

[0107] The photopolymerization initiator can be used to initiate polymerization by absorbing ultraviolet rays and generating free radicals or cations.

[0108] The photopolymerization initiator may include a photopolymerization initiator selected from benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-propan-1-one, 4-(2-hydroxyethoxy)phenyl- At least one or more of the group consisting of 2(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal and p-dimethylaminobenzoate, but not necessarily limited thereto.

[0109] The UV radiation dose can be about 1000mW / cm 2 About 1500mW / cm 2 The irradiation speed is about 30 mm / s to about 40 mm / s, and the preferred dose is about 1050 mW / cm 2 to about 1450mW / cm 2 The irradiation speed is about 32 mm / s to about 38 mm / s, and the more preferred dose is about 1100 mW / cm 2 to about 1400mW / cm 2 , the irradiation speed is about 33 mm / s to about 37 mm / s. When ultraviolet irradiation is performed under the above conditions, the mixture for forming the composite resin portion is completely cured, thereby forming a strong electrode protection material on the solid electrolyte layer where the positive electrode is not provided, and the step generated due to the area difference between the negative electrode and the positive electrode can be effectively eliminated.

[0110] Meanwhile, the ultraviolet ray irradiation may be performed for about 20 seconds to about 30 seconds, preferably about 22 seconds to about 27 seconds.

[0111] The viscosity of the mixture for forming the composite resin part may be about 10,000 Cp to about 15,000 Cp, preferably about 10,500 Cp to about 14,500 Cp, and more preferably about 11,000 Cp to about 14,000 Cp. When the mixture for forming the composite resin part has the above viscosity, the formed lower structure and the composite resin part can be completely cured, thereby improving the electrode protection function of the electrode protection member.

[0112] In addition, the mixture for forming the composite resin part may have a solid content of about 10% to about 15%, preferably about 10.5% to about 14.5%, and more preferably about 11% to about 14%, based on the total weight of the mixture. When the mixture for forming the composite resin part has this solid content, the formed lower structure and the composite resin part can be completely cured, thereby improving the electrode protection function of the electrode protection member.

[0113] The present invention will be described in more detail below by way of examples. However, these examples are only used to help understand the present invention, and the scope of the present invention is not limited to these examples in any way.

[0114] <Example 1> Manufacturing of an all-solid-state battery including an electrode protective material 1

[0115] An all-solid-state battery is manufactured as follows: a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer and a negative electrode current collector are stacked in sequence. Aluminum (Al) is used as a positive electrode current collector, a positive electrode layer including a positive electrode active material, a conductive material and a binder is prepared, and an oxide is used as a positive electrode active material.

[0116] In addition, a sulfide-based solid electrolyte with high lithium ion conductivity is used on the solid electrolyte layer. The negative electrode layer located on one side of the solid electrolyte layer is formed by coating a carbonaceous material (negative electrode active material) on a nickel-containing metal film (negative electrode current collector).

[0117] In this case, the area of ​​the positive electrode layer is formed to be approximately 90% to 95% of the area of ​​the solid electrolyte layer.

[0118] Next, the carbon nanotubes reacted with hydrogen peroxide to prepare a lower structure coated with hydroxyl groups, and the lower structure was placed on the area difference between the solid electrolyte membrane and the negative electrode, that is, the area where the negative electrode was not placed on the solid electrolyte membrane. Then, it was rolled at 25°C and a pressure of 4MPa for 7 seconds.

[0119] A mixed slurry for forming a composite resin part is coated on the lower structure, the mixed slurry including an acrylate-based polymer as an ultraviolet curing compound and a polyurethane-based polymer as a thermosetting compound in a weight ratio of 1:0.4.

[0120] Next, at 1200 mW / cm 2The composite resin composition slurry was completely cured by irradiating ultraviolet rays for 25 seconds at an illumination intensity of 100 nm and a speed of 35 mm / s.

[0121] <Example 2> Manufacturing of an all-solid-state battery including an electrode protective material 2

[0122] An electrode protective material and an all-solid-state battery were manufactured in the same manner as in Example 1, except that the weight ratio of the ultraviolet curable compound to the thermosetting compound was 1:0.6.

[0123] <Example 3> Manufacturing of an all-solid-state battery including an electrode protective material 3

[0124] An electrode protective material and an all-solid-state battery were manufactured in the same manner as in Example 1, except that the weight ratio of the ultraviolet curable compound to the thermosetting compound was 1:1.

[0125] <Comparative Example 1> Production of an All-Solid State Battery Including an Electrode Protective Material 4

[0126] An electrode protective material and an all-solid-state battery were manufactured in the same manner as in Example 1, except that only a thermosetting compound was used without using an ultraviolet curing compound.

[0127] <Comparative Example 2> Production of an All-Solid State Battery Including an Electrode Protective Material

[0128] An electrode protective material and an all-solid-state battery were manufactured in the same manner as in Example 1, except that only an ultraviolet curing compound was used without using a thermosetting compound.

[0129] <Reference Example 1> Manufacture of an all-solid-state battery including an electrode protective material 6

[0130] An electrode protective material and an all-solid-state battery were manufactured in the same manner as in Example 1, except that the weight ratio of the ultraviolet curable compound to the thermosetting compound was 1:2.5.

[0131] <Reference Example 2> Manufacture of an all-solid-state battery including an electrode protective material 7

[0132] An electrode protective material and an all-solid-state battery were manufactured in the same manner as in Example 1, except that the weight ratio of the ultraviolet curable compound to the thermosetting compound was 1:1.67.

[0133] <Comparative Example 3> Production of an All-Solid State Battery Without Electrode Protective Material

[0134] An all-solid-state battery was manufactured in the same manner as in Example 1, except that the composite resin composition slurry was not coated on the lower structure and cured.

[0135] <Experimental Example 1> Evaluation of the degree of curing and penetration into the solid electrolyte layer according to the weight ratio of the ultraviolet curable resin and the thermosetting resin

[0136] The electrode protective materials of the all-solid-state batteries according to Example 1, Example 2, Comparative Example 1, Comparative Example 2, Reference Example 1 and Reference Example 2 were immersed in a solvent of tetrahydrofuran (THF). Thereafter, the gel fraction of the composite resin composition and whether the resin penetrated into the solid electrolyte layer were observed according to the weight ratio of the ultraviolet curable resin and the thermosetting resin contained in the composite resin part, as shown in Table 1 below.

[0137] Here, the gel fraction is a value calculated by the following equation 1, W 0 is the weight of the sample before immersion (g), W 24 is the weight of the sample (g) after immersion for 24 hours.

[0138] [Equation 1]

[0139]

[0140] Furthermore, the penetration of the resin of the composite resin portion into the solid electrolyte layer was evaluated with the naked eye, and the penetration resistance was evaluated using the following ratings.

[0141] ◎: It was confirmed that there was no resin penetration at all.

[0142] ○: Almost no resin penetration was confirmed.

[0143] △: Slight penetration of the resin was confirmed.

[0144] X: Obvious penetration of the resin was confirmed.

[0145] [Table 1]

[0146] Reference Figure 3A As shown in Table 1, in the case of Examples 1 to 3 where the weight ratio of the ultraviolet curable resin to the thermosetting resin in the composite resin portion satisfies the range of 1:0.4 to 1:1, the gel fraction is 80%. Above, little or no resin penetrates into the solid electrolyte layer. In particular, in Examples 1 and 2 satisfying the range of 1:0.4 to 1:0.6, the gel fraction is 100%, and the resin of the composite resin portion does not penetrate into the solid electrolyte layer at all. On the contrary, in the case where the weight ratio of Comparative Example 1, Comparative Example 2, Reference Example 1, and Reference Example 2 exceeds the above numerical range, only part of the composition is converted into gel form, and part of the composition penetrates into the solid electrolyte layer.

[0147] also, Figure 3B and Figure 3C The SEM and CT imaging results of the electrode protection member portion of the all-solid-state battery according to Example 1 and Comparative Example 1 are respectively shown. In Example 1, it was confirmed that the components of the composite resin portion did not penetrate into the solid electrolyte, while in Comparative Example 1, it was confirmed that penetration into the solid electrolyte occurred.

[0148] <Experimental Example 2> Performance evaluation of all-solid-state batteries including electrode protective materials

[0149] The capacity retention rate of the all-solid-state batteries including the electrode protection materials according to Example 1 and Comparative Example 3 according to the cycle progress was measured, as shown in FIG. Figure 4 Here, the discharge is at 200 mA / cm 2 Up to 300mA / cm 2 carried out under the conditions of.

[0150] As the cycle progresses, it is confirmed that the capacity retention rate of Example 1 is superior to that of Comparative Example 3. This is because the electrode protection material is firmly positioned in the step formed by the size difference between the positive and negative electrodes, thereby effectively suppressing the components in the composite resin part from penetrating into the solid electrolyte.

Claims

1. An electrode protection member, comprising a lower structure comprising a carbon-based host, a surface of which comprises or is functionalized with one or more hydroxyl groups; and The composite resin portion is provided on the lower structure, and the composite resin portion includes a thermosetting resin and an ultraviolet curing resin. 2 . The electrode protection member according to claim 1 , wherein the carbon-based body is a carbon-based tubular body. 3 . The electrode protection member according to claim 1 , wherein the lower structure is a porous plate-like structure in which a plurality of the carbon-based bodies are connected to each other through point contacts. 4 . The electrode protection member according to claim 2 , wherein the lower structure is a mesh plate-like structure in which a plurality of the carbon-based bodies are irregularly connected. 5 . The electrode protection member according to claim 2 , wherein the lower structure is a grid-like plate-like structure in which a plurality of the carbon-based bodies are regularly connected. The electrode protection member according to claim 1 , wherein the carbon-based body is solid or hollow. 7 . The electrode protection member according to claim 1 , wherein the carbon-based body includes at least one or more selected from the group consisting of carbon fibers, carbon nanotubes, graphene, and mixtures thereof. 8 . The electrode protection member according to claim 1 , wherein a surface of the carbon-based body is functionalized with a hydroxyl group by treatment with a peroxide-based compound. 9 . The electrode protection member according to claim 1 , wherein the thermosetting resin is a polyurethane-based polymer. 10 . The electrode protection member according to claim 9 , wherein the polyurethane-based polymer contains an OH functional group and an NCO functional group in a molar ratio of 1:1.4 to 1:1.

8. 11 . The electrode protection member according to claim 1 , wherein the ultraviolet curable resin comprises an acrylate-based polymer, a reactive diluent, and a photopolymerization initiator. 12 . The electrode protection member according to claim 1 , wherein the ultraviolet curable resin and the thermosetting resin are contained in a weight ratio of 1:0.4 to 1:

1. 13 . The electrode protection member according to claim 3 , wherein the porous plate-like structure has a porosity of 60% to 95%. 14 . The electrode protection member according to claim 1 , wherein an average thickness of the lower structure is 10 μm to 40 μm. 15 . The electrode protection member according to claim 1 , wherein the carbon-based body in the lower structure and the thermosetting resin in the composite resin portion are connected to each other through a urethane bond.

16. An all-solid-state battery, comprising: negative electrode; A solid electrolyte layer disposed on the surface of the negative electrode; A positive electrode disposed on the surface of the solid electrolyte layer; as well as The electrode protection member according to claim 1, wherein the electrode protection member is provided on a surface of the solid electrolyte layer on which the positive electrode is not provided. 17 . The all-solid-state battery according to claim 16 , wherein the area where the electrode protection member is provided is 5% to 10% of the contact area between the negative electrode and the solid electrolyte layer.

18. A method for manufacturing an all-solid-state battery, the method comprising the following steps: In a laminate, a lower structure is arranged and rolled on a surface of a solid electrolyte layer where no positive electrode is arranged, the lower structure comprising a carbon-based body whose surface is functionalized with or contains hydroxyl groups, wherein the laminate comprises a negative electrode, a solid electrolyte layer arranged on the surface of the negative electrode, and a positive electrode arranged on the surface of the solid electrolyte layer; placing a mixture comprising a thermosetting compound and an ultraviolet curing compound on the lower structure, and curing the thermosetting compound; as well as The ultraviolet curable compound is cured by irradiating the mixture with ultraviolet rays to form a composite resin portion.

19. The method according to claim 18, wherein the calendering is performed at a temperature of 20 to 30°C and a pressure of 2 to 6 MPa.

20. The method according to claim 18, wherein the dose of ultraviolet radiation is 1000 mW / cm 2 Up to 1500mW / cm 2 , a speed of 30 mm / s to 40 mm / s, and a viscosity of the mixture for forming the composite resin part is 10,000 Cp to 15,000 Cp.

Citation Information

Patent Citations

  • Vacuum Interrupter

    KR1020230108575A